PG114 The importance of simulation on patient safety and human factors during a global pandemic. (10th November 2020) - Trimble, Alice; Vaughton, Andrew; Woodward, Lynsey; Wiggins, Jessica; Smith, Dominic; Tattam, Ali
Abstract : Introduction: The arrival of COVID-19 required a rapid, coordinated response by the entire theatre department at Royal Bournemouth Hospital (RBH) to adapt protocols, work in unfamiliar roles and manage increased demands on the service alongside significant anxiety amongst staff. It was recognised that team simulation training was key to addressing patient safety by embedding new guidelines surrounding the management of COVID-19 patients. Project Description: The theatre simulation faculty at RBH is a group of anaesthetists and operating department practitioners (ODPs) working together to deliver regular theatre simulation to the theatre team. A lack of engagement with simulation has, at times, limited attendance at these sessions. Witnessing the pressures faced by critical care systems across Europe in managing patients with COVID-19 prompted the creation of new teams, protocols and ways of working. The importance of simulation to support staff training to acquire extra skills, follow new procedures and in the management of significant human factors (magnified by PPE and staff anxiety) was addressed very quickly. Patient safety was at the centre of all training. Daily training sessions were set up, led by the simulation faculty. Staff were timetabled through a programme including simulation of 'Intubation Team' protocols, simulated proning, basic ITU principles and COVID -19 theatre pathways. The simulation sessions allowed every member of the multi-disciplinary team (anaesthetists, surgeons, ODPs, nurses and health care support workers) to practice working in their own, well-defined roles alongside the other members of the team. To compliment the timetabled sessions, online resources were created including a filmed version of simulated intubation of a COVID-19 patient by the intubation team. These online resources became invaluable once the importance of social distancing was understood, limiting team training. Outcomes: Running the daily sessions allowed the faculty to see the immediate effects of multi-disciplinary simulation on team morale. With every run through of the protocols, staff anxiety levels improved and familiarity with kit and process meant that, when COVID-19 patients started to present, they were safely and efficiently intubated by a confident and cohesive team. This was all echoed in the feedback collected during teaching and in wellbeing sessions during the pandemic. Discussion: The teaching sessions have awakened a desire within the department for team simulation and work has started to increase frequency of in-situ simulation training. Alongside this, an innovative online 'Simulated Anaesthetic Scenarios' resource¹² has been created to provide visual, real-time simulation to compliment written guidelines. References: Simulated Anaesthetic Scenarios https://www.sashealthcare.solutions. https://rcoa.ac.uk/simulation-resources.